Counter Psychological Warfare in the partisan press during the operations of Mosul liberation: An analytical study in the “Tareek Al Shaab” Newspaper - Rashid, Omar Adil; Johnny, Basim Waheed (ALBAHITH ALALAMI, 2023)
The research aims to monitor the methods of Counter psychological warfare in the Iraqi press during the operations to liberate Mosul from the control of the terrorist organization ISIS.The research used the survey method, and “Tareek Al Shaab” Newspaper as a research sample, chosen according to the systematic random sample.The research reached the following results:1- The Communicator’s relied on the contents of the counter-psychological warfare and its methods in the battle of “Qadimun Ya Naynawa” used in the newspaper. The methods used were labels assigning such as : inevitable victory, prodding and morale, consensus, breaking of opposition morale, stereotyping, demonization of the opponent, strength presentation, justification, emphasizing, distortion, emotionalization, and direct refusal. These methods came in varying proportions.2- The analysis revealed the reliance of the counter psychological warfare on the method of emotional inducements in a large proportion, focusing on addressing the Iraqi people.